2014
DOI: 10.1155/2014/873527
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Natural Pregnancy after Microsurgical Reconstruction in Patients with Primary Epididymal Obstructive Azoospermia

Abstract: Primary epididymal obstructive azoospermia (OA) is the most prevalent form of OA in nonvasectomized patients and has been less studied. We aim to assess the results with microsurgical vasoepididymostomy used in the treatment of men diagnosed with primary epididymal obstructive azoospermia and to identify the factors associated with natural pregnancy occurring after microsurgical reconstruction. This prospective study included consecutive patients with epididymal OA who underwent microsurgical reconstruction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All included studies were published between 1978 and 2021, with a cohort size ranging from 8 to 255 patients. Among them, 16 studies were conducted in China, five in Japan, 15 in America, four in India, two in Korea, two in Sweden, two in Saudi Arabia, one in Canada, one in Belgium, one in Egypt, one in Romania, and one in Slovenia, 4–9,12–56 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were published between 1978 and 2021, with a cohort size ranging from 8 to 255 patients. Among them, 16 studies were conducted in China, five in Japan, 15 in America, four in India, two in Korea, two in Sweden, two in Saudi Arabia, one in Canada, one in Belgium, one in Egypt, one in Romania, and one in Slovenia, 4–9,12–56 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Sperm parameters are the primary factors used to assess male sterility. Previous studies by Harza et al () and Peng et al () found that post‐operative sperm parameters are predictors of pregnancy after MVE. However, the optimal analysis time after MVE when sperm parameters show the greatest predictive value remains uncertain.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, the macroscopic evaluation of epididymal fullness is not objective or precise. In our opinion, motile spermatozoa in the epididymal fluid is more likely to be associated with higher patency and pregnancy rates (Harza et al ., ). In this study, 14 of 17 (82.4%) men with motile spermatozoa, compared with 10 of 22 (45.5%) men with immotile spermatozoa in the epididymal fluid, showed patency post‐operatively.…”
Section: Discussionmentioning
confidence: 97%